Gambaran Tingkat Pendidikan Dan Pengetahuan Tentang Perawatan Neonatus Pada Ibu Nifas Di Kecamatan Baki Kabupaten Sukoharjo - Nugraha, Satria Mulya; Dr. Faizah Betty RA., Dr. Faizah Betty RA.S.Kep., M.Kes; , Agustaria Budinugroho S. kep., Ns (2016)
neonates is very important because determine next development. implementation caring of neonates is needed a good knowledge by mother. Mother's knowledge can obtained from formal school. The results from pre study obtained there are mother still doesn't know to care for her neonates include umbilical cord, temperature, skin treatment, eye treatment , breastfeeding and neonates. The objectives is to know relationship between Education level to knowledge level of caring of neonates in Kecamatan Baki of Sukoharjo. Design study use quantitative escriptive. A method with cross sectional approach. The population study was all the mother puerperium who have neonates at community health, on November 2015. Samples were 30 mothers who had a neonates with taking sample use purposif. Instrument use questionnaire and check list. Data were analysis using central tendency.The survey result revealed a median value of 11 mode 10 minimum 8 maksimum 13. And most of the respondent have a good knowledge. Keyword: education level, knowledge, caring neonates, mother puerperium